Corrosion of 15Mo3 carbon steel superheater tubes in waste incineration plants: A comparison between a field‐returned tube and laboratory tests. Issue 1 (18th November 2019) - Krumm, Ludmilla; Galetz, Mathias C.
Abstract: In this study, a field‐returned superheater tube of carbon steel 16Mo3 (1.5415) was analyzed in detail. In addition to cross‐section analysis, different scales were investigated layer by layer using microscopic, diffraction, and spectroscopic techniques. The corrosion products can be divided into three layers: The layer adjacent to the metallic tube surface was an iron‐ and chlorine‐rich scale, followed by an FeS layer present at the gas flow side, and the outermost layer was an iron oxide scale consisting of Fe3 O4 and α‐Fe2 O3 . The different mechanisms responsible for the structure of such scale formation and the different corrosion products formed at the tube are discussed. Furthermore, the root cause for the disability to form a protective scale under such conditions was identified by comparison with results from laboratory tests. Abstract : A field‐returned superheater tube of carbon steel 16Mo3 was analyzed in detail. The layer adjacent to the metallic tube surface was an iron‐ and chlorine‐rich scale, followed by an FeS layer present at the gas flow side, and the outermost layer was an iron oxide scale consisting of Fe3 O4 and α‐Fe2 O3 . The different mechanisms responsible for the structure of such scale formation and the different corrosion products formed at the tube are discussed. The schematic composition of corrosion products beneath the deposit on a field‐returned superheater tube of 16Mo3.